Teleología del deseo : un ensayo fenomenológico (2010)
ABSTRACT: Moral rationalism has accustomed us to understand the past in terms of personal reasons for acting. In this sense, it is said human action is rational because it can account for their motives. This principle, extrapolated into the future, understands existential projects as deliberative planning. The phenomenology of action and corporality set out a more complex problem on the relationship between a plan and its implementation, having into account physical and intersubjective conditions of projects, as well as its elusive face when pursuing a merely conceptual articulation of them. This paper aims to develop a phenomenology of these tensions between any project and its execution in two sections: (a) the existence as a project, and (b) such an existence and the structured project: the limits of discourse.